1959
DOI: 10.1113/jphysiol.1959.sp006254
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and fate of radioactive histamine in the rat

Abstract: It is universally accepted that histamine, whether of endogenous or exogenous origin, is disposed of by the two processes of enzymic destruction and of excretion through the renal tract. There is, however, little information about the way in which exogenous histamine is brought into contact with its specific enzymes. The rapid clearance of histamine from the blood after its intravenous injection (Rose & Browne, 1938) suggests that the uptake of histamine by the tissues may be a method for its immediate disposa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1962
1962
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…These results are compatible with the 50% disappearance of histamine during one circulation (15-20 s) in all vascular beds of the dog (Table 1, Figure 3). Halpern et al (1959) also found that more than 50% of circulating histamine disappears within 30 s in the rat. This rapid disappearance of histamine from the circulation must be due to its removal or inactivation by tissues (Rose & Brown, 1938;Emmelin, 1951) and, as indicated in this paper, does not depend on blood pressure.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…These results are compatible with the 50% disappearance of histamine during one circulation (15-20 s) in all vascular beds of the dog (Table 1, Figure 3). Halpern et al (1959) also found that more than 50% of circulating histamine disappears within 30 s in the rat. This rapid disappearance of histamine from the circulation must be due to its removal or inactivation by tissues (Rose & Brown, 1938;Emmelin, 1951) and, as indicated in this paper, does not depend on blood pressure.…”
Section: Discussionmentioning
confidence: 79%
“…The bulk of the histamine taken up by tissues is catabolized in situ. However, some tissues may release it back to the circulation when it will be metabolized by other tissues or excreted by the kidneys (Emmelin, 1951;Halpern et al, 1959;Green, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, all organs which have been examined, including the heart, take up histamine (Mannaioni, 1972). The first evidence of cardiac histamine uptake was given by Halpern, Newen & Wilson (1959) showing that after intravenous injection into rats the largest concentrations of the amine were found in the heart, lung, liver and kidney, mostly reflecting tissue blood flow. Further insight into the uptake of histamine by hearts of different animal species was afforded by in vivo studies on the fate of labelled histamine after intravenous infusion into the mouse and rat (Snyder, Axelrod & Bauer, 1964; Reilly & Schayer, 1970;1971), cat (Johnson, Beaven, Erjavec & Brodie, 1966) and dog (Ryan & Brody, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a considerable amount of histamine is still excreted unmodified (35,37), and in humans, cases of histamine intolerance due to ingestion of spoiled fish (40) or other amine-rich foods (41), endogenous histamine overproduction, or an imbalance between the accumulation of histamine and its elimination are known to result in elevated plasma histamine levels and severe allergic reactions (41) or recurrent anaphylaxis (42). This suggests that histamine exceeds its physiological usefulness during exposure to large amounts of it, and this overwhelms the inactivation mechanisms, causing unwanted effects on blood pressure, vascular tone, and permeability.…”
Section: Figurementioning
confidence: 99%